CdSe/CdSe1–xTex core/crown heteronanoplatelets : tuning the excitonic properties without changing the thickness - Kelestemur, Yusuf (2020)
Here we designed and synthesized CdSe/CdSe1-xTex core/crown nanoplatelets (NPLs) with controlled crown compositions by using the core-seeded-growth approach. We confirmed the uniform growth of the crown regions with well-defined shape and compositions by employing transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray diffraction. By precisely tuning the composition of the CdSe1-xTex crown region from pure CdTe (x = 1.00) to almost pure CdSe doped with several Te atoms (x = 0.02), we achieved tunable excitonic properties without changing the thickness of the NPLs and demonstrated the evolution of type-II electronic structure. Upon increasing the Te concentration in the crown region, we obtained continuously tunable photoluminescence peaks within the range of ∼570 nm (for CdSe1-xTex crown with x = 0.02) and ∼660 nm (for CdSe1-xTex crown with x = 1.00). Furthermore, with the formation of the CdSe1-xTex crown region, we observed substantially improved photoluminescence quantum yields (up to ∼95%) owing to the suppression of nonradiative hole trap sites. Also, we found significantly increased fluorescence lifetimes from ∼49 up to ∼326 ns with increasing Te content in the crown, suggesting the transition from quasi-type-II to type-II electronic structure. With their tunable excitonic properties, this novel material presented here will find ubiquitous use in various efficient light-emitting and -harvesting applications.